Update in TIGIT Immune-Checkpoint Role in Cancer - Annese, Tiziana; Tamma, Roberto; Ribatti, Domenico (Frontiers in Oncology, 2022)
The in-depth characterization of cross-talk between tumor cells and T-cells in solid and hematological malignancies will have to be considered to develop new therapeutical strategies concerning the reactivation and maintenance of patient-specific antitumor responses within the patient tumor microenvironment. Activation of immune cells depends on a delicate balance between activating and inhibitory signals mediated by different receptors. T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT) is an inhibitory receptor expressed by regulatory T cells (Tregs), activated T cells, and natural killer (NK) cells. TIGIT pathway regulates T cell-mediated tumor recognition in vivo and in vitro. TIGIT blockade as monotherapy or in combination with other drugs is emerging in clinical trials in patients with cancer. The purpose of this review is to update the role of TIGIT in cancer initiation and progression. TIGIT pathways are often upregulated, related to tumor aggressiveness and drug resistance. Therefore, TIGIT represents an exciting target for checkpoint blockade immunotherapy.